Workplace Environment and Islamic Ethics as Foundations for Field Performance: Lingkungan Kerja dan Etika Islam sebagai Landasan Kinerja di Lapangan - Azzahra, Amelia; Supriyaningsih, Okta; Fasa, Muhammad Iqbal (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: In the digital era, employee performance is critical to the sustainability of organizations, particularly in sectors such as telecommunications. Specific Background: At PT Telkom Kedaton Branch, field employees face high-risk environments that demand optimal performance supported by conducive workplace conditions. Knowledge Gap: While previous studies have examined physical factors affecting performance, few have integrated ethical dimensions rooted in Islamic business principles. Aims: This study aims to investigate the influence of workplace environment, occupational safety, and health on employee performance through a holistic framework incorporating Islamic values. Results: Using multiple linear regression with 49 respondents, findings show that workplace environment has the strongest influence, followed by occupational safety and health, all of which significantly improve employee performance. Novelty: This research uniquely integrates Islamic business ethics—such as justice, trustworthiness, and social benefit—into occupational safety and health analysis, offering a spiritually grounded approach to human resource management. Implications: The study suggests that organizations, especially in high-risk sectors, should adopt ethical, holistic policies that integrate spiritual values to enhance employee well-being, satisfaction, and organizational resilience.Highlight : The workplace environment has the strongest influence on employee performance. Safety and health programs contribute positively, though to a lesser extent. Islamic business values enrich workplace practices and employee well-being. Keywords : Workplace Environment, Occupational Safety, Health, Employee Performance, Islamic Business Perspective